Important Tips to Improve the Impacts of a Research Paper: Pre and Post Publication Strategies - Safavi-Naini, Amir Ahmad; Aghdaee, AmirHossein (Student Research in Translational Medicine, 2023)
We do research projects to expand human knowledge and solve real-world problems. Well said, Scott Fitzgerald, “an unread book is just a block of paper.” Researchers should increase the visibility of their paper; otherwise, the value of a research paper is limited to just a file and a Doi. Here we presented some tips for authors to improve the visibility and citation number of their research [1]. The tips are gathered by reviewing the literature [2–8] and asking expert opinions. After publication Most of the researchers think that getting the acceptance of their research manuscript in a good journal is their final endeauver. They Although the best time for improving future scientific metrics of a paper is before publication, there are ways to increase the visibility of research after publication. A.1. Research communities and social media You can share your article in social media conducted for scientific communities (i.e., LinkedIn, Research gate, Elsevier, Mendeley, Google Scholar, ORCID). Moreover, sharing your research on Twitter boosted the citation number by 43% [9]. You can gain the interest of your audience by sharing an exciting piece of your findings and providing the link to the article on your social media or webpage (Check with publisher first). Inserting audio or text content from your paper on the web may give a 50% increase the paper’s citation [2]. Articles covered in the news get 13 times higher citation numbers [10]. Therefore, you can increase the visibility of the research paper by contacting a journalist to cover your work. -Cont.